The Influence of Cow Puerperal Infections Considering the Main Reproduction Indicators - Valeriu Caraba; Nicolae Pacala; Nicolae Corin; Ioan Bencsik; Bujor Avramescu; Ramona Untaru; Alexandra Ivan (Scientific Papers Animal Science and Biotechnologies, 2023)
This article it’s presenting results regarding the main reproduction indicators for German Spotted and Frizz Holstein. In stand to achieve this goal we fallow 3 main reproduction indicators to the cows with normal uterine involution and to the cows with puerperal infections: uterine repose (UR), Insemination index (Ig) and gestation rate (G). Regarding the uterine repose we notice that there were no significantly differences between the two breeds for the cows with normal uterine involution, 114.00±8.80 days for German Spotted and 126.79±12.86 days for Frizz Holstein. For the cows with puerperal infections we notice very significant differences, 128.58±10.16 days for German Spotted and 184.27±12.68 days for Frizz Holstein. Regarding the number of insemination/gestation there were no significant differences between the cows with normal calving. In this way, the index/gestation was 1.45±0.11 for German Spotted and 1.57±0.17 for Frizz Holstein. For the cows with puerperal infections was a distinguished significant difference regarding the index/gestation, so we have 1.59±0.16 for German Spotted and 2.32±0.20 for Frizz Holstein. The pregnancy rate for the cows with normal uterine involution was 66% for German Spotted and 64% for Frizz Holstein. The gestation rate for Frizz Holstein was smaller for both categories (64% at the cows with normal uterine involution and 42% at the cows with puerperal infection). After that research we can conclude that, generally, the cows with post calving infections registered middle values for different reproduction indicators comparative with the healthy cows.